IMPLEMENTATION OF THE POLICY OF REGIONALIZATION OF EDUCATION IN THE ACTIVITIES OF THE UNIVERSITY - S. V. Kosenok (Высшее образование в России)
The strategic objective of Surgut State University is its transformation into a new type of university, supporting and providing innovative economic development of the region through concentration of intellectual potential, modern scientific and educational infrastructure which meet the requirements of regional business. Such modernization is determined by the policy of the Government of Khanty-Mansiysk Autonomous Okrug –Yugra, according to which education sector is regarded as the most important resource for the development of the region. This determines the necessity to improve the model of the third mission of a university – Community Service.